Increased thalamic gray matter volume induced by repetitive transcranial magnetic stimulation treatment in patients with major depressive disorder - Wang, Zhongheng; Zhang, Dongning; Guan, Muzhen; Ren, Xiaojiao; Li, Dan; Yin, Kaiming; Zhou, Ping; Li, Baojuan; Wang, Huaning (Frontiers in Psychiatry, 2023)
Purpose: Repetitive transcranial magnetic stimulation (rTMS) is an effective therapy in improving depressive symptoms in MDD patients, but the intrinsic mechanism is still unclear. In this study, we investigated the influence of rTMS in brain gray matter volume for alleviating depressive symptoms in MDD patients by fMRI. Methods: Patients with first-episode, unmedicated patients with MDD (n=26) and healthy controls (n=31) were selected for this study. Depressive symptoms were assessed before and after treatment by using the HAMD-17 score. Resting-state functional magnetic resonance imaging (rs-fMRI) data were collected before and after treatment to compare the changes in brain gray matter volume. Results: Before treatment, patients with MDD had significantly reduced gray matter volumes in the right fusiform gyrus, left and right inferior frontal gyrus (triangular part), left inferior frontal gyrus (orbital part), left parahippocampal gyrus, left thalamus, right precuneus, right calcarine fissure, and right median cingulate gyrus compared with healthy controls (P<0.05). After rTMS treatment, a significant growth in grey matter volume of bilateral thalamus was observed in depressed patients (P<0.05). Conclusion: MDD patients had reduced gray matter volumes in frontal-temporal-parietal regions, as after rTMS treatment bilateral thalamic volumes were significantly increased. These changes in neuroimaging indicators may reveal the potential neural mechanism for rTMS to improve depressive symptoms